1974
DOI: 10.1029/wr010i002p00303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partial penetration on flow in unconfined aquifers considering delayed gravity response

Abstract: Previously, a new analytical model was proposed by the author for the delayed response process characterizing flow to a well in an unconfined aquifer. It was shown that contrary to prevailing belief this process can be simulated by using constant values of specific storage and specific yield without recourse to unsaturated flow theory. In the present work the theory is extended to account for the effect of a well partially penetrating a homogeneous anisotropic unconfined aquifer. Field and laboratory evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
405
2
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(423 citation statements)
references
References 19 publications
10
405
2
6
Order By: Relevance
“…Kollet and Zlotnik (2005a,b) showed that re-infiltration and resulting aquifer return flow was likely during the pumping test and studied the effect on parameter estimates. They used three-dimensional analytical (e.g., Neuman 1974) and numerical models in their analysis of PT. Their estimates of the hydraulic conductivity (K≈100 m/day) agree well when compared to results in the section Results of time-drawdown data analysis, despite that simpler two-dimensional models were used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kollet and Zlotnik (2005a,b) showed that re-infiltration and resulting aquifer return flow was likely during the pumping test and studied the effect on parameter estimates. They used three-dimensional analytical (e.g., Neuman 1974) and numerical models in their analysis of PT. Their estimates of the hydraulic conductivity (K≈100 m/day) agree well when compared to results in the section Results of time-drawdown data analysis, despite that simpler two-dimensional models were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…3. The measured time-drawdown behavior is characteristic of unconfined aquifers and exhibits the three distinct drawdown phases that are attributed to the interaction of compressible aquifer storage and the vertical movement of the free water-table surface in the unconfined aquifer (Neuman 1972 and1974).…”
Section: Time-drawdown Data and Analysismentioning
confidence: 99%
“…Hydraulic properties were estimated using a type-curve fitting method according to the analytical solution of Neuman (1972Neuman ( , 1974Neuman ( , 1975 for an unconfined aquifer with delayed gravity response (specific yield). In this analysis, the wells can be either partially or fully penetrating.…”
Section: Constant-rate Injection Testsmentioning
confidence: 99%
“…The analysis approach is based on type-curve matching methods (i.e., Neuman 1972Neuman , 1974Neuman , 1975 that are commonly used to analyze standard pumping test responses. These approaches, however, do not account for wellbore storage effects either at the pumped well or observation well locations.…”
Section: 16mentioning
confidence: 99%